Motivation Of Paraprofessionals In University Libraries In Ghana: The Case Of Valley View University And University Of Professional Studies, Accra - Opoku-Larbi, L. (University of Ghana, 2015)
Motivation of paraprofessionals is pertinent for excellent service delivery in the library since they constitute the first point of call to any patron who enters the library. The study therefore looks at motivation of paraprofessionals in selected academic libraries in Ghana. The study used a case study approach that involved unstructured interviews to solicit information from 24 paraprofessional library staff at Valley View University (VVU) and University of Professionals Studies, Accra (UPSA). Generally, studies on motivation abound in literature. However, many of these studies focus less on paraprofessional library staff. Thus, this study attempts to determine the motivation packages available to paraprofessionals in VVU and UPSA, to find out how these packages impact the work of paraprofessionals in VVU and UPSA, and to determine whether paraprofessionals are satisfied with their job or not and find out what motivates paraprofessionals intrinsically and extrinsically. The findings show that while VVU has motivation packages for paraprofessionals, UPSA has none. Further, the findings show that the paraprofessionals considered recognition for good work, opportunities for promotion, flexibility of schedule and reimbursement of tuition as good motivation incentives. The most propelling motivators in the findings were acknowledgment for a decent work done, followed by schedule flexibility while library social gathering was the least of all the factors. Also, it was revealed that paraprofessionals would still want to stay in the library despite the lack of motivation. It is, therefore, recommended that opportunities such as more seminars and workshops should be organised for paraprofessionals at least once every academic calendar. Besides, the feeling of insecurity as far as their employment was concerned also emerged. Strategies have been suggested on how to manage the low self-image of paraprofessionals and how to deal with high job turnover among paraprofessionals due to lack of motivation.. It was recommended among others that a policy statement that define motivation packages for paraprofessionals should clearly be outlined in a document which would show what paraprofessionals in UPSA are entitled to and it should be tailored to their needs.Furthermore, stakeholders especially the library management should give recognition to paraprofessionals for good work done by setting targets for them, and when these targets are met, library management should make it a point to reward them. If this is done a lot can be gained from them.
Thesis (MPhil)
Keywords: Motivation Of Paraprofessionals; University Libraries In Ghana; Valley View University; University Of Professional Studies; Accra; Ghana